2007
DOI: 10.1097/01.mcg.0000248018.08515.f9
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Patients With End-stage Liver Disease

Abstract: Infections in patients with end-stage liver disease (ESLD) are an important cause of morbidity and mortality in these patients. Abnormalities in their natural defense mechanisms, alterations in the enteric flora and the growing utilization of invasive procedures increase the risk of infections in these patients. Common bacterial infections in ESLD patients include spontaneous bacterial peritonitis, urinary tract infections, community-acquired pneumonia, dermatologic infections, and bacteremia. Viral infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 78 publications
3
45
1
2
Order By: Relevance
“…39 Our study did not confirm such an association, but this may be related to the very low number of patients reporting a history of hepatic disease. Renal dysfunction has been reported to be a risk factor for invasive aspergillosis in lung transplant recipients.…”
contrasting
confidence: 55%
“…39 Our study did not confirm such an association, but this may be related to the very low number of patients reporting a history of hepatic disease. Renal dysfunction has been reported to be a risk factor for invasive aspergillosis in lung transplant recipients.…”
contrasting
confidence: 55%
“…All of the seven patients with liver disease suffered from invasive aspergillosis, which reflected their immunocompromised status and the presence of additional risk factors for S. maltophilia colonization, such as antibiotic therapy. As such, those seven patients are at risk of infections precipitated by the significant impairment of the neutrophil defence mechanism, frequent use of corticosteroids and invasive procedures, and malnutrition (Panasiuk et al, 2005;Cheruvattath & Balan, 2007;Falcone et al, 2011;Fishman, 2011;Barchiesi et al, 2015). However, to the best of our knowledge, our study is the first description of an association between co-infection by A. fumigatus and S. maltophilia and patients with liver disease.…”
Section: Discussionmentioning
confidence: 45%
“…Bacterial infections are recognized as a significant cause of morbidity and mortality in this population; 7,11,46 the most commonly reported bacterial infections are spontaneous bacterial peritonitis (SBP), urinary tract infections, pneumonia, bacteremia, and skin and soft tissue infections. 3,5,42 Prospective studies have found that 13%Y20% of bacterial infections in patients with cirrhosis are caused by pneumonia.…”
Section: Introductionmentioning
confidence: 99%